Optimization of Activated Carbon Synthesis from Spent Coffee Grounds for Enhanced Adsorption Performance - Geon-Woong Hyeon; Gi Bbum Lee; Da Jung Kang; Sang Eun Lee; Kwang Mo Seong; Jung-Eun Park (Molecules)
As an adsorbent, biomass activated carbon is effective at the removal of a wide range of organic and inorganic pollutants; however, its synthesis remains complex. Although spent coffee grounds (SCG) could be an effective material for the production of activated carbon, achieving a sufficient surface area has proven to be difficult. Here, this study presents a preliminary investigation into the optimal manufacturing conditions of activated-carbon adsorbents derived from SCG. SCG samples were characterized according to proximate analysis, elementary analysis, surface area, and pore volumes, then subjected to various processes (i.e., drying, carbonization, and chemical activation) with different operating parameters (temperature and time). The samples were optimized as follows: (1) Stable drying of SCG with a high moisture content of approximately 65% required consumption energy of 49 kWh/kg and drying at 105 °C for 20 h. (2) By comparing changes in the consumption energy and product yield with an increasing amount of carbon fraction, it was found that drying carbonization was more suitable than hydrothermal carbonization for SCG. The optimum drying carbonization temperature for achieving attractive biochar was 500 °C for 1 h. (3) Activated carbon with the optimum surface area (3687 m2/g) and mesopore volume fraction (approximately 70%) was achieved with a chemical activator agent ratio of approximately 3 and heating at 850 °C for 1 h. Furthermore, the butane working capacity of the activated carbon was related to the mesopore volume/surface area and reached 74.5% at a mesopore volume/surface area of 0.0004, indicating its suitability for activated carbon canisters. These findings can be used to optimize the synthesis of industrial-grade activated carbon from SCG.